TerraServer Cluster and SAN Experience - Barclay, Tom; Gray, Jim (2004)
Microsoft TerraServer stores aerial, satellite, and topographic images of the earth in a SQL database available via the Internet since June 1998. It is one of the most popular online atlases, presenting seventeen terabytes of image data from the United States Geological Survey (USGS). Initially the system demonstrated the scalability of PC hardware and software Windows and SQL Server on a single, mainframe-class processor. In September 2000, the back-end database application was migrated to 4-node active/passive cluster connected to an 18 terabyte Storage Area Network (SAN). The new configuration was designed to achieve 99.99% availability for the back-end application. This paper describes the hardware and software components of the TerraServer Cluster and SAN, and describes our experience in configuring and operating this system for three years. Not surprisingly, the hardware and architecture delivered better than 4-9s of availability, but operations mistakes delivered 3-9s.